2001
DOI: 10.1159/000064335
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Transplantable Melanoma Cells to Cytokines with Regard to Their Spontaneous Apoptosis

Abstract: Objectives: Changes in the sensitivity of two lines of transplantable melanoma cells to the antiproliferative activity of interleukin 6 (IL-6), oncostatin M (OSM), tumor necrosis factor-α (TNF-α) during melanoma progression were the subject of this study. We were looking for a correlation between these changes and the ability of melanoma cells to undergo spontaneous apoptosis. Methods: The influence of exogenous cytokines on the proliferation of melanoma cells was measured by colorimetric methods with MTT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…These results, taken together with the threefold higher activity of caspase-3 19 and lower ability to undergo spontaneous apoptosis in amelanotic melanoma cells observed in our earlier works, 18,19 may indicate that the cells of this line have mechanism(s) inhibiting activated caspases, e.g., some proteins from IAP family, as suggested by other authors for human melanoma cells. 26 Our earlier findings, where over fourfold fewer cells of amelanotic melanoma line from S/G 2 /M phases died spontaneously, in comparison to melanotic melanoma line, suggest that proliferating amelanotic melanoma cells, in particular, have mechanism(s) protecting them from apoptosis.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results, taken together with the threefold higher activity of caspase-3 19 and lower ability to undergo spontaneous apoptosis in amelanotic melanoma cells observed in our earlier works, 18,19 may indicate that the cells of this line have mechanism(s) inhibiting activated caspases, e.g., some proteins from IAP family, as suggested by other authors for human melanoma cells. 26 Our earlier findings, where over fourfold fewer cells of amelanotic melanoma line from S/G 2 /M phases died spontaneously, in comparison to melanotic melanoma line, suggest that proliferating amelanotic melanoma cells, in particular, have mechanism(s) protecting them from apoptosis.…”
Section: Discussionsupporting
confidence: 83%
“…The loss of pigment was accompanied by changes in many biological features of the amelanotic melanoma line-faster tumor growth rate, shorter animal survival and changes in ultrastructure of cells. 9,18 Once established, these melanomas possessed a considerable degree of phenotypic stability over decades of passaging. 9 Since their discovery, each melanoma line is maintained in vivo by consecutive, subcutaneous transplantations of tumor material every 21 (Ma) or 11 (Ab) days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Susceptibility of melanoma cells to apoptosis may be related to their ability to synthesize NO; recently, it was shown that inhibition of NO synthesis induces apoptosis in melanoma cells (31). Our earlier results demonstrated that Ab are able to synthesize NO more vigorously than the Ma line; thus it is possible that endogenous NO is promoting survival of the Ab cells (32). However, these observations do not explain increased activity of caspase‐3 in the same cell line especially since NO is reported to inhibit caspases in other cell systems, thus decreasing apoptosis (4, 33, 34).…”
Section: Discussionmentioning
confidence: 95%
“…Since then, the Ab hamster melanoma line has been maintained in vivo by consecutive subcutaneous transplantations of tumor material [ 73 , 74 , 75 ]. The hamster Ab melanoma cells were obtained for each experiment from solid tumors using a non-enzymatic method of cell isolation, as previously described [ 76 ]. The resection of the tumor was performed after 10–11 days of growth after the transplantation.…”
Section: Methodsmentioning
confidence: 99%